Analysis of the Effectiveness of General Services Retribution Revenue and Its Contribution to Local Revenue of Mataram City - M. Alif Husain; Abdul Manan; Eka Agustiani; Gaghman , AbdulGhani (Journal of Social and Humanities, 2024)
This study aims to analyze the growth rate and effectiveness of general service levy revenue, the contribution of general service levies to local retribution, and the contribution of both general service levies and local retribution to the Local Revenue (PAD) of Mataram City from 2018 to 2022. This research employs a quantitative descriptive approach. The analysis revealed that the growth rate of the general service levy in Mataram City between 2019 and 2022 showed positive growth, but the increase was minimal, with an average growth rate of only 13.86% (categorized as Unsuccessful). The effectiveness ratio of general service levy revenue from 2018-2022 averaged 61.53%, indicating a "Less Effective" performance. This suggests that the Mataram City Government has been largely unsuccessful in achieving its general service levy revenue targets. While general service levies have made a significant contribution to local retribution, with an average contribution of 85.26% (categorized as Very Good), their contribution to Mataram City's PAD is still inadequate, averaging only 4.39% (categorized as Very Lacking). Similarly, the contribution of local retribution to Mataram City's PAD remains insufficient, with an average contribution of 5.16% (categorized as Very Insufficient). Moving forward, it is recommended that the Mataram City Government implement both intensification and extensification policies to improve the collection of general service levies, thereby increasing their contribution to PAD. Future research should extend beyond a 5-year period to provide more comprehensive insights and clearer trends.